A Legal Economics Analysis of Dental Implant Pooling - Gao, Yuan (International Journal of Global Economics and Management, 2024)
With the improvement of living standards and the deepening of population aging, China's demand for dental implants has continuously shown double-digit high-speed growth, while the field of charging irregularities, the heavy burden of costs and other issues are also increasingly prominent. In 2022, the National Health Insurance Bureau issued a notice stating that it will carry out a set of procurement of dental implant consumables, and determined that the price of the whole process of regulating the price of medical services for a single conventional implant in a three-tier public hospital is targeted at 4,500 yuan. In January 2023, the inter-provincial coalition of dental implant procurement led by the Sichuan Provincial Health Insurance Bureau under the guidance of the National Health Insurance Bureau opened the bidding in Chengdu, and the average price of the winning products was reduced by 55%. Known as "the most difficult collection in history" landing, marking the first attempt to achieve the collection of high-value consumables from the field of medical insurance expansion to the field of non-medical insurance, but also a large number of private dental institutions involved in the collection. Dental implant collection for the whole industry chain may bring the impact of triggered a continuous debate, whether it can achieve "volume for price" to promote capacity upgrading or compression of profits lead to the constraints of industry innovation still need time to prove.